Comparative Proteomic Analyses Between Biofilm-Forming and Non-biofilm-Forming Strains of Corynebacterium pseudotuberculosis Isolated From Goats - Sá, Maria Conceição Aquino de; Silva, Wanderson Marques da; Rodrigues, Carla Catarine Santos; Rezende, Cristiana Perdigão; Marchioro, Silvana Beutinger; Rocha Filho, José Tadeu Raynal; Sousa, Thiago de Jesus; de Oliveira, Helinando Pequeno; Costa, Mateus Matiuzzi da; Figueiredo, Henrique César Pereira; Portela, Ricardo Dias; Castro, Thiago Luiz de Paula; et al. (Frontiers in Veterinary Science, 2021)
Caseous lymphadenitis (CLA) is a chronic disease that affects small ruminants and causes economic losses in the associated breeding system. The causative agent of CLA is Corynebacterium pseudotuberculosis, a Gram-positive bacterium that exhibits tropism for external and internal lymph nodes and induces abscess formation in the host. Bacterial communities often produce a biofilm matrix that serves various functions, including protection against hostile environmental conditions, antibiotics, and the host immune response. Although biofilm formation has been reported for C. pseudotuberculosis, not all strains demonstrate this property in culture. In this work, we report the first comparative proteomic analysis of one biofilm-forming (CAPJ4) and one biofilm-non-forming strain (CAP3W) of C. pseudotuberculosis isolated from goats. Bacterial whole cell protein extracts were obtained for mass spectrometry analyses. Using LC-MS/MS, our studies reveal three and four proteins exclusively found in the CAPJ4 and CAP3W proteome, respectively. In addition, label-free quantitative analysis identified 40 proteins showing at-least two-fold higher values in CAPJ4 compared CAP3W proteome Notably, CAPJ4 differentially synthesized the penicillin-binding protein, which participates in the formation of peptidoglycans. CAPJ4 also exhibited upregulation of N-acetylmuramoyl-L-alanine amidase and galactose-1-phosphate uridylyltransferase, which are involved in biofilm formation and exopolysaccharide biosynthesis. Here, we demonstrate that biofilm formation in C. pseudotuberculosis is likely associated with specific proteins, some of which were previously shown to be associated with virulence and biofilm formation in other organisms. Our findings may drive studies related to the bacterial mechanisms involved in the biofilm formation, in addition to providing targets for the treatment of CLA.